Family Education Using a Booklet Improved Medication Adherence in Hallucinating Patients in the Waipare Public Health Center Area - Theresia Silvia Kidi; Yuldensia Avelina (STIKES Syedza Saintika Padang, 2026)
Auditory hallucinations were a primary symptom in patients with severe mental disorders and could disrupt social functioning, sleep patterns, and increase the risk of harmful behavior if not properly managed. Medication non-adherence was one of the main factors contributing to relapse and was often influenced by a lack of understanding and insufficient family support. This case study aimed to describe the implementation of a family education intervention using a booklet to improve medication adherence among patients with auditory hallucinations in the working area of Waipare Public Health Center.The study employed a case study approach using the nursing process, which included assessment, diagnosis, planning, implementation, and evaluation. The subjects consisted of two patients with auditory hallucinations and their families as primary caregivers, who were selected through purposive sampling. The intervention was conducted over three days through home visits by providing health education using a booklet that contained information about the definition of hallucinations, the importance of medication adherence, medication side effectsKeywords: Auditory hallucinations; Booklet; Family education; Medication adherence